Criminal Acts Of Attempted Rape Yanng Resulting In A Sense Of Fear ( See Also Decision No. 474 / Pid/2013 / Pt-Mdn) - Sahputra, Rilawadi; Basri, Hasan (Legalpreneur Journal, 2025)
Sexual violence is a serious offense that involves the coercion of sexual relations without consent, and affects victims in various aspects of their lives. In Indonesia, coercion of sexual relations with violence or threats against women outside of marriage is a complex social problem. The issue of sexual violence, especially involving attempts to force a woman to have sex outside of marriage through violence or threats of violence, has become a profound problem and affects many aspects of human life, both legally, socially, and psychologically. These actions not only violate human rights, but also reflect the deep gender inequality in society. This study aims to examine the phenomenon from three main perspectives: legal, social, and psychological. From a legal perspective, the sexual coercion of a woman outside of marriage through violence or the threat of violence constitutes a serious violation of the laws governing human rights and the protection of women. In this context, in Indonesia, sexual violence is regulated in law No. 12 of 2022 on the crime of sexual violence (TPKS), which provides greater protection for victims and establishes more severe sanctions for perpetrators. Socially, this phenomenon highlights the structural injustices that often occur, in which victims are often blamed or ignored by society, as well as the existence of social stigma towards victims of sexual violence. Patriarchal social norms and gender inequality further exacerbate this situation, leading many victims to feel isolated and afraid to report the violence they experience. From a psychological perspective, sexual coercion can leave a deep traumatic impact on the victim. Such Trauma not only affects the emotional and mental state of the victim in the short term, but can also continue in the long term, affecting interpersonal relationships, and overall mental health. Psychological disorders such as post-traumatic stress disorder (PTSD), depression, anxiety, as well as feelings of inferiority are often experienced by victims of sexual violence. This study aims to provide a more comprehensive picture of the interaction between these three perspectives and how legal, social, and psychological factors play a role in shaping victim experiences as well as in sexual violence prevention and response efforts. Thus, the results of this study are expected to contribute to the development of more effective policies in addressing the problem of sexual violence, as well as increasing public awareness of the importance of protecting women and the mental well-being of victims of sexual violence.